Performance, Presentations, and Rhetoric: Incorporating Rhetorical Theory into a Postgraduate Academic Communication Skills Course for EFL Learners - Tyler Carter (Cranmore Publishing, 2019)
In this discussion of a recent course design at Duke Kunshan University, a Sino-American joint university located in Kunshan, China, rhetorical theory is used to facilitate the development of academic presentation skills in the context of an EFL Academic Communication Skills (ACS) course for postgraduate students. Specifically, audience awareness, the rhetorical situation, kairos, and visual design are used to help students develop fluency, confidence, and rhetorical effectiveness in academic presentations. The article begins with a discussion of the teaching context, a rationale for the innovations described, and an explication of the course content before expanding on how theories from the disciplines of rhetoric can be applied to academic presentations. In the end, the author argues that incorporating rhetorical theory into an ACS course is not a replacement for a language-centric approach to teaching presentation skills, but a necessary supplement that will help prepare postgraduate students for academic and professional careers.